2022
DOI: 10.1152/ajpendo.00366.2021
|View full text |Cite|
|
Sign up to set email alerts
|

Development of a synbiotic that protects against ovariectomy-induced trabecular bone loss

Abstract: The gut microbiome has the capacity to regulate bone mass. The aim of this study was to develop a synbiotic dietary assemblage at an optimal dose to maintain bone mass in ovariectomized (Ovx) mice. We performed genomic analyses and in vitro experiments in a large collection of bacterial and fungal strains (>4000) derived from fresh fruit and vegetables to identify candidates with the synergistic capacity to produce bone-protective short-chain fatty acids (SCFA) and vitamin K2. The candidate SBD111, composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The construction of SBD111 included genomic annotation of food-derived strains for functions shown to modulate bone remodeling (e.g., short chain fatty acid and vitamin K2 production) as well as in silico screening for safety based on the absence of characterized virulence factors. The component strains of this consortium act in a synergistic manner; i.e., SBD111 produces a greater amount of acetate than the sum of its individual components [12]. In addition, we showed that administration of the medical food, SBD111, signi cantly reduced trabecular bone loss in a mouse model of post-menopausal osteoporosis, using ovariectomized (Ovx) mice compared to vehicle controls [12].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The construction of SBD111 included genomic annotation of food-derived strains for functions shown to modulate bone remodeling (e.g., short chain fatty acid and vitamin K2 production) as well as in silico screening for safety based on the absence of characterized virulence factors. The component strains of this consortium act in a synergistic manner; i.e., SBD111 produces a greater amount of acetate than the sum of its individual components [12]. In addition, we showed that administration of the medical food, SBD111, signi cantly reduced trabecular bone loss in a mouse model of post-menopausal osteoporosis, using ovariectomized (Ovx) mice compared to vehicle controls [12].…”
Section: Introductionmentioning
confidence: 88%
“…In a recent publication, we described the design and characterization of SBD111, a synbiotic medical food consortium of bacterial and fungal isolates derived from fresh fruits and vegetables, in addition to prebiotic dietary bers [12]. The construction of SBD111 included genomic annotation of food-derived strains for functions shown to modulate bone remodeling (e.g., short chain fatty acid and vitamin K2 production) as well as in silico screening for safety based on the absence of characterized virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…Teklad diet 2016 does not contain alfalfa or soybean meal, thus minimizing the occurrence of natural phytoestrogens that can interfere in studies of castration-induced bone loss. We made the decision to use the C57BL/6J mouse strain since we used this strain in earlier studies of the effect of probiotic bacteria on castration-induced bone loss and wanted to be able to compare the results ( Ohlsson et al 2014 , 2021 , Lawenius et al 2020 , 2022 ). At 12 weeks of age, the mice were randomized into four groups ( n = 13–15) and subjected to orx or sham surgery under inhalation anesthesia with isoflurane (Baxter Medical AB, Kista, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…At 12 weeks of age, the mice were randomized into four groups ( n = 13–15) and subjected to orx or sham surgery under inhalation anesthesia with isoflurane (Baxter Medical AB, Kista, Sweden). The number of mice in each group was decided based on experience from earlier studies with similar treatments and parameters studied ( Ohlsson et al 2014 , 2021 , Lawenius et al 2020 , 2022 ). In these studies, we found small but consistent effects on the bone with the number of observations ranging from 8 to 15 per group.…”
Section: Methodsmentioning
confidence: 99%
“…Solarea Bio has generated multiple pre-clinical validations of product efficacy in mouse models of osteoporosis. 13 While the SBD111 product has been tested in multiple preclinical studies and a toxicity study in rats, it has yet to be administered to a human volunteer. An adverse event profile of this product is a necessary first step to advance it to the next phase of clinical development.…”
Section: Introductionmentioning
confidence: 99%